From "Experiments of Concern" to "Groups of Concern": Constructing and Containing Citizens in Synthetic Biology. (November 2020) - Frow, Emma
Synthetic biology represents a recent and explicit attempt to make biology easier to engineer, and through this to open up the design space of genetic engineering to a wider range of practitioners (including, but not limited to, engineers). Proponents of this approach emphasize the standardization of practices as key to successful biological engineering; yet, meaningful transatlantic differences are emerging with respect to the constitution of key concerns and the governance of synthetic biology in the United States (US) and the United Kingdom (UK). In this article, I tease out how national approaches to governing synthetic biology are being framed against different salient past experiences with recombinant DNA technology. In the US, the governance of synthetic biology is consistently articulated in relation to the early days of recombinant DNA technology and the self-governance mechanisms pioneered in response to Asilomar. In the UK, more recent experiences with genetically modified crops provide the overarching imaginary against which governance initiatives are being proposed. I suggest that these differing sociotechnical imaginaries have implications for how new "groups of concern" are being defined in relation to synthetic biology and how measures to contain perceived risks are being pursued in the US and Britain.